British Army Logistics in the Burma Campaign 1942-1945 - Dunlop, Graham (The University of Edinburgh, 2007)
The logistical challenges facing the British imperial Army in the Burma campaign of 1942-1945 were formidable, yet there has been no comprehensive, scholarly study of the campaign from a logistic point of view. The aim of this thesis, therefore, is to examine logistic influences on the design, conduct and outcome of British operations in Burma in order to demonstrate the relative importance of logistics to the final victory. The thesis comprises three parts. Part one looks at the British retreat from Burma inl942, as well as India's economic and military position at that time, in order to establish the foremost logistic problems that had to be solved before the war could be taken back to the Japanese. India was ill-fitted to become the strategic base for further operations; the operational lines of communication in the north east of the country were inadequate; and, at the tactical level, suitable means of maintaining forces in the jungle were lacking. Part two examines the building of the base infrastructure in India; the improvement of the lines of communication; and the evolution of air, water and animal-borne supply during 1942 and 1943. Part three assesses the impact of these developments on the conduct and outcome of operations in 1944 and 1945. It shows that the strategic timetable of the campaign until 1944 was dictated mainly by the progress achieved in assembling the resources and solving the problems identified in part one. It reveals that the direction of operations thereafter was determined as much by the alignment and capacity of the lines of communication, and the need to control them, as by strategic intentions and enemy actions. It demonstrates the crucial importance of the methods developed in tactical supply to the achievement of success on the battlefield. Overlaid on all the above, the thesis indicates that the priority attached to maintaining and expanding the supply line to China, as well as the shortage of amphibious and air transport resources, had a decisive impact on the strategic and operational conduct of the campaign.